Comparative Study On The Prevalence Of Trichodiniasis And Monogeniasis In Clarias gariepinus (Burchell, 1822) Of Different Age Groups In The University Of Calabar Fish Farm And Its Implication To Fish Farmers - Asuquo, Philomena Edet; Eyo, Victor Oscar (Journal of Survey in Fisheries Sciences, 2023)
The objective of this study was to comparatively evaluate the prevalence of trichodiniasis and monogeniasis in the African Catfish Clarias gariepinus of the different age groups from the University of Calabar fish farm, Cross River State, Nigeria. A total of three hundred (300) C. gariepinus samples of different age groups (100 fingerlings, 100 juveniles, and 100 adults) were collected with hand net necropsied for parasitological analysis. Skin, gill, and fin biopsies were prepared from each collected sample following standard methods for microscopic analysis. The results showed that of three hundred (300) C. gariepinus examined from different age groups 22 fish (13 fingerlings, 6 juvenile and 3 adults) were infested with 62 ectoparasites (36 in fingerlings, 16 in juveniles and 10 in adults) belonging to Trichodina heterodentata and Gyrodactylus sp. with an overall prevalence of 7.33 %. The impact assessment of parasites showed that the abundance, intensity, and prevalence were higher in fingerlings (0.36, 2.77 and 13.00%), followed by juveniles (0.16, 2.67 and 6.00%) and lowest in adults (0.10, 3.33 and 3.00%). In the three age groups of fish, T. heterodentata and Gyrodactylus sp. were most prevalent in the gills and least likely in the skin, suggesting that the gills are their most preferred external organ. The results of this study showed that trichodiniasis and monogeneasis are more common in C. gariepinus of a lower age group with implication on the general welfare of the fish. Therefore, to prevent the outbreak of trichodiniasis and monogeneasis, standard quarantine procedure, water quality management, good nutrition, adequate stocking density, and proper hygienic conditions is recommended.
Keywords: Ectoparasitic infestation; Trichodina heteredontata; Gyrodactylus sp.; Disease outbreak; Huge monetary loss; Standard quarantine procedure